Planetary Secularisms: Delayed Messianism, Climate Change, and the Space for Pluralism - Bauman, Whitney (Dialog, 2015)
As many scholars have pointed out, Western secularism (or neoliberalism) is itself a faith-filled and religiously located concept. It forces other understandings of secularism (and along with it other religions) to adhere to the public reason/private faith distinction, for instance, or else face the charge of being unenlightened or somehow in the dark (ages). This article agrees with and builds upon these ongoing critiques of secularism by suggesting that the two important bio-historical factors that are beginning to shed light on the religiously filled foundations of Western-style secularity are those of globalization and climate change. The contemporary situation of globalization and climate change is forcing the hidden faith of secularism out of its foxhole.